2006
DOI: 10.1093/jac/dkl244
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of gentamicin in premature newborns

Abstract: The two-compartment open model was found to significantly better describe gentamicin pharmacokinetics in the neonate. More than PNA or GA, creatinine clearance (CLCR) plays an important role in the elimination of gentamicin in premature newborns. Creatinine clearance is also related to GA. The appropriate dosing regimens given in accordance with the characteristics of the patients are 5 mg/kg/48 h and 4 mg/kg/24 or 36 h for neonates<32 weeks and >or=32 weeks of GA, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 23 publications
5
45
0
Order By: Relevance
“…BW also increases significantly during the first year of life; therefore, the introduction of such a covariate in the population pharmacokinetic analysis allows for a comparison of V with that of other populations. The mean value obtained for this parameter is in accordance with that of other studies, being lower than that reported for adult populations (0.28 liters/kg) and higher than that given for newborns (0.48 liters/kg) (27,28).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…BW also increases significantly during the first year of life; therefore, the introduction of such a covariate in the population pharmacokinetic analysis allows for a comparison of V with that of other populations. The mean value obtained for this parameter is in accordance with that of other studies, being lower than that reported for adult populations (0.28 liters/kg) and higher than that given for newborns (0.48 liters/kg) (27,28).…”
Section: Discussionsupporting
confidence: 91%
“…This population of infants exhibits different characteristics than those of newborns or adults (13,27,28). In the current study, the population pharmacokinetic parameters of gentamicin were retrospectively estimated by NONMEM 7.2 in a total population of 263 infants who were admitted to the Hospital Universitario Severo Ochoa (Leganés, Spain) between the years 1990 and 2011 and who received gentamicin as part of their treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deriving a Bayesian prior for TDM requires a nonlinear mixed-effect PK model, and several such studies of neonatal gentamicin were previously published (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, those studies were limited by their heterogeneity and use of sparse data (often identifying only a 1-compartment model, whereas gentamicin follows multicompartment kinetics [25,26]) and failed to account for age-related differences in creatinine levels during the immediate newborn period.…”
mentioning
confidence: 99%